The Incredible ULKs: Autophagy and Beyond - Zhao, Yan G.; Zhang, Hong (Molecular cell, 2016)
Atg1 integrates nutrient status and autophagy. In this issue, Joo et al. (2016) reveal that the mammalian Atg1 homologs ULK1/2 are dispensable for neuronal basal autophagy. ULK1/2 phosphorylate SEC16A and regulate ER export, expanding the autophagy-independent functions of autophagy proteins. Atg1 integrates nutrient status and autophagy. In this issue, Joo et al. (2016) reveal that the mammalian Atg1 homologs ULK1/2 are dispensable for neuronal basal autophagy. ULK1/2 phosphorylate SEC16A and regulate ER export, expanding the autophagy-independent functions of autophagy proteins.